Stevioside improves brain oxidant-antioxidant status in overfed zebrafish - ALTURFAN, EBRU IŞIK (My University, 2023)
Objective: An excessive buildup of adipose tissue is a defining feature of overnutrition, and a significant fraction of the world’s population suffers from obesity. Overnutrition is associated with the deterioration of mitochondrial functions in the brain in the case of obesity. In this study, we evaluated the effects of stevioside (ST) which is a calorie-free, naturally occurring herbal sweetener made from Stevia rebaudiana (Bertoni) on the oxidant-antioxidant balance in the brain in cases of overnutrition. Accordingly, the effects of ST consumption on the oxidant-antioxidant balance in the brain was evaluated and determined in a case study of overfeeding adult zebrafish for 15 days. Materials and Methods: Zebrafish were placed in four groups; the control group (C); overfed group (OF); low-dose (1mg/L) ST treated OF group (OF+LDS); and the high-dose ST (5mg/L) treated OF group (OF+HDS). The levels of lipid peroxidation (LPO) were evaluated together with nitric oxide (NO) to determine the oxidant status. The antioxidant status from the activities of the superoxide dismutase (SOD) and glutathione S-transferase (GST) were determined in brain tissues. Results: The ST treatment decreased the increased LPO and NO levels in overfed zebrafish and increased SOD and GST activities in a dose-dependent manner. Conclusion: ST exerted an antioxidant effect on the possible damage mechanisms that could occur in the brain in case of overnutrition by decreasing oxidative stress and improving the antioxidant enzyme activities.
Keywords: Beslenme ve Dietetik; Yaşam Bilimleri; Biyokimya; Sağlık Bilimleri; Temel Bilimler; Nutrition and Dietetics; Life Sciences; Biochemistry; Health Sciences; Natural Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Tarım Bilimleri; Doğa Bilimleri Genel; Biyoloji ve Biyokimya; BESLENME VE DİYETETİK; ÇOK DİSİPLİNLİ BİLİMLER; BİYOKİMYASAL ARAŞTIRMA YÖNTEMLERİ; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); Natural Sciences (SCI); Life Sciences (LIFE); AGRICULTURAL SCIENCES; NATURAL SCIENCES, GENERAL; BIOLOGY & BIOCHEMISTRY; NUTRITION & DIETETICS; MULTIDISCIPLINARY SCIENCES; BIOCHEMICAL RESEARCH METHODS; Beslenme ve Diyetetik; Multidisipliner; Multidisciplinary; Stevioside; overfeeding; brain; oxidant-antioxidant status; zebrafish